Digital Marketing Strategy for Sales Volume of PT. AMJ Sukses Propertindo's Minimalist Cluster Housing in Bekasi - Heri Geri Sugeri; Tuwis Hariyani (⁠⁠Jurnal Literasi Indonesia, 2024)
This study aims to analyze the implementation of digital marketing strategies in increasing the sales volume of minimalist cluster housing at PT. AMJ Sukses Propertindo in Bekasi. The research employs a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data collection, reduction, presentation, and conclusion drawing. The findings indicate that digital marketing strategies, particularly through social media platforms (Instagram, Facebook, and TikTok), Search Engine Optimization (SEO), and Search Engine Marketing (SEM), play a significant role in generating leads and increasing consumer interest, especially among millennials. Social media content such as virtual open houses, development progress updates, and promotional offers effectively attracts potential buyers. SEO contributes to increasing organic website traffic, while SEM generates high-intent leads despite rising advertising costs. Supporting factors include integrated teamwork, responsive management, and effective customer service, whereas inhibiting factors involve limited human resources, budget constraints, and economic fluctuations. Overall, the implementation of digital marketing strategies has contributed positively to improving sales performance, although continuous innovation and optimization are required to achieve sustainable growth.